A scalable electron beam irradiation platform applied for allotropic carbon transformation. (15th April 2021) - de Campos da Costa, João Paulo; Teodoro, Vinícius; Assis, Marcelo; Bettini, Jefferson; Andrés, Juan; Pereira do Carmo, João Paulo; Longo, Elson
Abstract: The design of solid-state materials whose properties and functions can be manipulated in a controlled manner by the application of electron beam irradiation is important in modern materials chemistry and physics. In this paper, we present a progress in the development of scalable electron beam irradiation platform to obtain innovative materials for technological and industrial applications, since one of the problems to be solved in this research area is the scalability of these new nanomaterials induced by electron beam irradiation (EBI). In particular, we focus on carbon structures due to its excellent and exciting properties applied in the technological area in the last years, where we show for the first time a new strategy for carbon allotropic transformation through the portable EBI. This new platform is particularly effective, fast, versatile, clean and easy-to-use, facilitating the preparation of many types of nanomaterials that cannot be obtained by conventional chemical and physical methods. The EBI on flat graphite pellets resulted in a covering of it surface with rod-like particles composed of different allotropic forms of carbon. Furthermore, the developed system allowed the implantation of the Fe as a catalytic material through steel sputtering of the high voltage acceleration anode during the EBI process. It was observed by HRTEM analyses that the rod-like particles are preferentially composed of highly oriented graphite in its bottom, polycrystalline graphite in its middle and magnetite nanoparticles in its top. Graphical abstract: Image 1